Ni‐Coated SiC Particles: Synthesis and Densification. Issue 12 (18th August 2015) - Nechiche, Mustapha; Gauthier‐Brunet, Véronique; Eyidi, Dominique; Azem, Said; Dubois, Sylvain
Abstract : The mechanofusion process, a dry particle coating route, has been successfully applied to coat micrometric SiC particles with submicrometric Ni filaments. In a first step, the mechanofusion parameters were optimized to form a continuous Ni coating onto SiC particles. In a second step, the Ni‐coated SiC particles were sintered by hot isostatic pressing. The temperature and pressure cycles were determined to ensure a good densification of the material. Such a densification process leads to the formation of a δ‐Ni2 Si bilayer at the SiC/Ni interface; the inner δ‐Ni2 Si layer in contact with SiC being more rich in carbon than the one in contact with the matrix. From X‐ray diffraction, wavelength‐dispersive X‐ray spectrometry and scanning electron microscopy characterizations, a mechanism is proposed to explain the microstructure of the end‐product.